2017
DOI: 10.25115/ejrep.v7i18.1325
|View full text |Cite
|
Sign up to set email alerts
|

Academic achievement and formal thought in engineering students

Abstract: Introduction. Research on university-level academic performance has significantly linked

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…The differences in results may be attributable to such factors as types of assessment, sample selection techniques, and sample size. The review of these studies revealed that only (Vázquez & Anglat, 2017), (Gurcay & Gulbas, 2018), and (Rakhmawan et al, 2018) used TOLT, other studies used different tests and revealed the same results that logical thinking had a significant relationship with science achievement. Another limitation of several studies is that their focus is restricted to logical thinking as a whole ability, except (Bitner-Corvin, 1988) study which was entered into the five modes of logical thinking into regression analysis.…”
Section: Definitions Of Termsmentioning
confidence: 96%
See 2 more Smart Citations
“…The differences in results may be attributable to such factors as types of assessment, sample selection techniques, and sample size. The review of these studies revealed that only (Vázquez & Anglat, 2017), (Gurcay & Gulbas, 2018), and (Rakhmawan et al, 2018) used TOLT, other studies used different tests and revealed the same results that logical thinking had a significant relationship with science achievement. Another limitation of several studies is that their focus is restricted to logical thinking as a whole ability, except (Bitner-Corvin, 1988) study which was entered into the five modes of logical thinking into regression analysis.…”
Section: Definitions Of Termsmentioning
confidence: 96%
“…He reported that the five logical thinking modes were predictors of academic achievement. In the same approach, (Vázquez & Anglat, 2017) study was carried out on a sample of (709) first-year engineering students from the Argentine university. They found that entrance exams and TOLT scores explained 26% of the variance in physics achievement.…”
Section: Definitions Of Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…Такође, у складу са очекивањима, школски успех високо позитивно корелира са свим супскалама ментализације, као и са скором на тесту логичких операција. Веза формално-операционалног мишљења и школских постигнућа потврђена је и у другим истраживањима (Vázquez & De Anglat, 2009;Mwamwenda, 2015).…”
Section: дискусијаunclassified